A cohort study of neurodevelopmental outcome in children with DiGeorge syndrome following cardiac surgery. Issue 1 (1st January 2003) - Maharasingam, M; Östman-Smith, I; Pike, M G
Abstract : Aims: To examine whether the learning difficulties seen in a proportion of children with DGS are secondary to cardiac pathology and treatment, or a feature of the DGS phenotype. Methods: Cohort study of all patients with DGS and coexisting cardiac lesions within a region. Ten children with 22q11 deletion were assigned two controls each, matched for age, sex, cardiac lesion, and preoperative hemodynamic status but without DGS. The neurodevelopmental status was evaluated with the Ruth Griffiths test for babies and young children. Results: Children with the 22q11 deletion showed a wide range of developmental quotient (DQ; mean 71, 95% CI 47 to 95) and subscale scores, but these as a group were significantly lower than those of the control group (DQ 113, 95% CI 108 to 118). Four of the DGS children had DQs below 60. Hypocalcaemia, prolonged postoperative ventilation, and abnormal neurology perioperatively were associated with a low DQ. Conclusions: A proportion of children with DGS have a very poor developmental outcome following cardiac surgery. This outcome is not attributable to the cardiac condition and its treatment alone, but represents either a pre-existing component of the syndrome or an interaction between the syndrome and its treatment.